What Every Systems Engineer Needs to Understand about Business Models. Issue 3 (October 2015) - Amon, Lee
ABSTRACT: Practitioners of systems engineering are facing challenges as daunting as any seen in the history of the field. In order to respond to these challenges effectively, and to leverage all the benefits possible from transformational systems engineering techniques, the Transformation Caucus believes that systems engineers must be part of the decision process at the business level. This paper discusses and examines several business models and the impacts of the business model chosen on the effectiveness of transformational systems engineering techniques.